Early Soviet Economic Border Controls: East-West Dimension - Ermolaeva, Oksana («Քոփի Փրինթ» տպ.)
In most studies early Soviet borders are explored as sites of confrontational interactions between the newly created communist state and local communities. Alternatively, they emerge in scholarly research as spaces of illegal transborder exchanges and commodities transfers, resulting in the loss of official revenues and gains for informal economies. Later, in increasingly politicized contexts, these interactions resulted in the gradual “cleansing” and “sealing” of borders. The current article argues that to regain control over the borders during their transition from bridgeheads of the revolution and commodity transit zones to hermetically sealed barriers and fortress walls that occurred throughout the 1920s - 1930s, the Soviet state for some time struggled in vain to discipline not only local communities, which used the newly created borders for their own means, but multiple border controllers themselves - border guards, but primarily the customs apparatus located along Russia’s lengthy borders. For almost a decade in the specific conditions of Eastern and Northwestern Soviet border sectors, the latter refused to abide to increasingly restrictive working conditions, abandon their privileges and rights, and to submit to the new border control agency - the Soviet Main Political Directorate (GPU). Ուսումնասիրությունների մեծ մասում վաղ խորհրդային սահմանները դիտարկվում են որպես նորաստեղծ կոմունիստական պետության և տեղական համայնքների միջև առճակատման վայրեր: Գիտական հետազոտություններում այդ տարածքները ներկայացվում են նաև որպես անօրինական անդրսահմանային փոխանակումների և ապրանքների փոխանցման տարածքներ, որոնք հանգեցնում էին պետական եկամուտների նվազման և անօրինական տնտեսությունների հարստացմանը: Հետագայում, ավելի ու ավելի քաղաքականացված համատեքստում, այս փոխազդեցությունները հանգեցրին սահմանների աստիճանական «մաքրման» և «կնքման»։
Keywords: Soviet border control; Economy